The transition from physiotherapy student to new graduate: are they prepared?. (2nd January 2022) - Stoikov, Susan; Maxwell, Lyndal; Butler, Jane; Shardlow, Kassie; Gooding, Mark; Kuys, Suzanne
ABSTRACT: Background : The transition from physiotherapy student to new graduate poses many challenges. In other health disciplines concerns have been raised about new graduate preparedness for practice. Objective : To explore the perspectives of new graduate and experienced physiotherapists on the transition from student to new graduate. Methods : Semi-structured interviews were conducted with 15 focus groups; nine new graduate groups and six experienced physiotherapist groups. Interviews were transcribed in preparation for thematic analysis whereby researchers examined transcripts independently and identified codes. Codes were compared and themes developed, discussed, and refined. Themes were reviewed by all authors. Results : Four themes emerged surrounding the transition from physiotherapy student to new graduate: 1) preparedness for practice; 2) protected practice; 3) independent and affirmation of practice; and 4) performance expectations. Both groups identified increased caseload volume and complexity were challenging, and that students were typically protected from realistic workloads. New graduates at times felt unprepared for their new roles and highlighted that coping with change in independence and managing expectations of themselves was difficult. Strategies identified that may assist the transition from student to new graduate included organizational, clinical placement experiences and building self-efficacy. Conclusions : Challenges are experienced during the transition from physiotherapy student to new graduate. To enhance this transition a multifactorial approach is required that includes all key stakeholders and strategically targets challenges associated with the student transition to new graduate.